Local Financing of Water Utilities : Challenges and Opportunities - The Case of Peru - World Bank (World Bank, 2012)
This report identifies opportunities and challenges for local financing of water utilities in Peru and suggests recommendations for removing barriers and creating incentives for scaling-up local financing to local water utilities. It was developed with an understanding that meeting the Millennium Development Goals (MDGs) in water and sanitation in Peru will require scaling up local financing for the sector and that efficiency and effectiveness can be enhanced by greater involvement of local institutional investors and other parties. This joint study exposes many of the barriers to local private financing facing the urban water supply and sewerage (WS&S) sector in Peru. In short, the majority of local water utilities cannot meet credit rating and governance standards required to access private financing. Consequently, loans from financial markets are rare. These findings are probably not specific to Peru. Accordingly, there is great value for central governments to undertake similarly detailed studies to identify the obstacles preventing access to local financing unique to their country's WS&S sector.